Nanoprisms: Gold Nanoprisms as Optoacoustic Signal Nanoamplifiers for In Vivo Bioimaging of Gastrointestinal Cancers (Small 1/2013). Issue 1 (3rd January 2013) - Bao, Chenchen; Beziere, Nicolas; del Pino, Pablo; Pelaz, Beatriz; Estrada, Giovani; Tian, Furong; Ntziachristos, Vasilis; de la Fuente, Jesus M.; Cui, Daxiang
<x xml:space="preserve">Abstract</x> On page 68, PEGylated gold nanoprisms are designed and prepared by J. M. de la Fuente, D. Cui, and co‐workers, with the aim to study the feasibility of using them as a novel contrast agent for the hybrid technique of optoacoustic imaging. The nanoprisms are imaged at different scales using different imaging modalities. They are confirmed as biocompatible, and selected colon cancer HT‐29 cells are used as research targets. Shown here is an in silico electron tomographic reconstruction of such gold nanostructures, which show promise for application in biomedical imaging, drug delivery, and photothermal therapy. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>